1993
DOI: 10.1213/00000539-199311000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Leg Warming Minimizes Core Hypothermia During Abdominal Surgery

Abstract: The efficacy of leg skin warming in preventing hypothermia and shivering was evaluated in two separate prospective, randomized trials in patients undergoing abdominal surgery. In the first trial, 22 patients were randomized to receive no hypothermia prevention (control group) or active warming with an electric warming blanket (electric blanket group). In the second trial 33 patients were randomized to receive no hypothermia prevention (control group) or forced-air warming (Bair Hugger group) or forced-air warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…11,12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The Mantel-Haenszel fixed effect model was used to compute robustness and susceptibility to any outlier among these trials. The allocation, concealment and blinding of the investigator or assessor were not clearly reported, and consequently the methodological quality of the trials was conRCTs retrieved for more detailed evaluation n = 25…”
Section: Resultsmentioning
confidence: 99%
“…11,12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The Mantel-Haenszel fixed effect model was used to compute robustness and susceptibility to any outlier among these trials. The allocation, concealment and blinding of the investigator or assessor were not clearly reported, and consequently the methodological quality of the trials was conRCTs retrieved for more detailed evaluation n = 25…”
Section: Resultsmentioning
confidence: 99%
“…This is the most commonly tested body warming modality and is unsurprisingly associated with significantly higher postoperative core temperatures when compared with patient control groups where no warming was used [41][42][43]. The dual benefit of transferring heat to the body and reducing heat losses [44] from the skin under the air warmer accounts for this finding.…”
Section: Forced-air Warmersmentioning
confidence: 99%
“…Unsurprisingly, when compared against passive insulation [90] or no warming [41,91], resistive heating achieves significantly higher patient core temperatures. Furthermore, when evaluated against forced-air warming, an early non-clinical investigation with healthy volunteers showed that the heat transfer achieved from resistive heating was significantly greater [92].…”
Section: Resistive Heatingmentioning
confidence: 99%
“…O segundo corresponde ao tremor associado à vasodilatação ou tremor não relacionado com a regulação térmica 13 . Observou-se que tremores não ocorrem apenas em pacientes hipotérmicos 14,15 , eles podem também acometer pacientes normotérmicos 2,16,17 e, em contraposição, muitos pacientes com hipotermia importante não apresentam tremores. Sessler e col. concluíram que o tremor pós-operatório tem origem na regulação térmi-ca 12 , é provocado por hipotermia e pode também ocorrer em indivíduos normotérmicos que estão desenvolvendo febre 15 .…”
Section: Introductionunclassified
“…Postoperative tremors can be of two types: the first corresponds to the tremor associated with thermal regulation that is associated with vasoconstriction, being a physiological response to central or peripheral hypothermia 11,12 that develops in the intraoperative period; the second corresponds to the tremor associated with vasodilation or tremor not associated with thermal regulation 13 . It has been observed that tremors do not affect only hypothermic patients 14,15 and they can also be present in patients whose temperature is normal 2, 16.17 and, on the other hand, many hypothermic patients do not develop tremors. Sessler et al concluded that postoperative tremors are secondary to thermal regulation 12 , are caused by hypothermia, and can also affect normothermic patients who are developing fever 15 .…”
Section: Introductionmentioning
confidence: 99%